Adhesion between self-affine rough surfaces: Possible large effects in small deviations from the nominally Gaussian case. (May 2017) - Ciavarella, M.; Papangelo, A.; Afferrante, L.
Abstract: It is shown that even small deviations from the ideal Gaussian random roughness case seem to lead to dramatic increase in adhesion of rough surfaces: this could be due to a finite number of asperities, or to a finite tail in the height distribution, particularly realistic at low fractal dimensions D, which is the case of most practical interest. It is emphasized that the assumption of a perfect Gaussian heigth distribution, including infinite tails, may be a strong one when studying adhesion in rough surfaces. Abstract : Highlights: Small deviations from the commonly assumed Gaussian model for the adhesion of rough surfaces may lead to dramatic effects in adhesion of rough surfaces. Finite number of asperities and finite extension of the tail of the height distribution are particularly sensitive parameters, also giving possible large scatter of results. The Gaussian model may be a strong assumption for real surfaces.